Family firm identity and capital structure decisions. Issue 2 (10th July 2017) - Thiele, Felix K.; Wendt, Martin
Abstract : Purpose: The purpose of this paper is to grasp the effect of familiness on capital structure decisions in family firms, as family firm identity may be an important source of competitive advantage due to its potential to moderate relationships with stakeholders such as banks. Design/methodology/approach: The paper uses panel data from 2010 to 2014, which combine financial and structural data on 691 large private German companies. The econometric approach is a random-effect and tobit panel regression using different dependent variables relating to debt. Findings: The study reveals that family firms have significantly higher overall and long-term debt levels compared to their non-family counterparts. Contrary to the extant literature, tangibility is not significantly related to debt in the context of family firms and the hypothesized higher usage of trade credits by family-owned businesses could not be supported. Research limitations/implications: Future research can improve the measurement of familiness by changing from a dichotomous to a continuous variable, acknowledging that family businesses are not homogenous. This would also enable a different econometric approach. Practical implications: A practical implication for family firms is to actively capitalize on their identity and thus, improving the way they present themselves towards different groups of stakeholders to mitigate information asymmetries and enhance trust. Originality/value: The paper investigates large private family-owned businesses, applies multiple dependent variables, and uses a family firm specific theoretical framework, namely familiness, to explain the family's influence on the business.